Efficacy of Daclatasvir and Half Dose Sofosbuvir in the Treatment of Hepatitis –C Virus Infection in Patients of Maintanance Hemodialysis-3 Years Trial in A Tertiary Renal Center (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Hepatitis C virus (HCV) infection in end-stage renal disease (ESRD) heralds a bad outcome. Directly acting antiviral (DAA) drugs sofosbuvir along with daclatasvir are very effective in the management of HCV infection. Sofosbuvir is excreted mainly through the kidneys. There is sparse data worldwide on the use of sofosbuvir based drug regimens in ESRD patients having chronic hepatitis C (CHC) virus infection.This study was designed to evaluate the efficacy of half dose sofosbuvir in the management of HCV infection in ESRD patients on maintenance hemodialysis (MHD).Methods: This clinical trial was conducted among 125 ESRD patients on MHD at Gonoshasthaya dialysis center, Dhanmondi, Dhaka from July 2019 to June 2022. Total 125 HCV positive patient with ESRD on MHD were included in this study; all the patients underwent HCV-RNA PCR test. Patients with detectable HCV RNA were observed for six months without antiviral drugs to identify the occurrence of spontaneous clearance of virus. Patients who had detectable HCV-RNA after six months were treated with sofosbuvir(200 mg) and daclatasvir (60 mg), irrespective of genotype. The drugs were given daily for 12 weeks. All the patients were on regular follow up at two weeks interval. Blood counts, liver function, creatinine phosphokinase and serum amylase values were evaluated periodically; virological response was assessed by HCV-RNA after 12 weeks of antiviral treatment.Results: During the observation period, 29 (23.2%) patients had spontaneous virus clearance with an undetectable HCV-RNA.  In the remaining 96 patients, the median HCV-RNA level was 2.76×104 (1.56 ×103– 1.89×106)I IU. Twelve weeks after the treatment, 91 (94.8%) patients achieved sustained virological response (SVR) with undetectable HCV-RNA. All patients tolerated the DAAs well and none of the patients reported any serious adverse events. No patient discontinued antiviral therapy due to side effects. Patients who attained SVR with DAA, after 6 months we repeated HCV-RNA in 30 patients, in majority of them (28, 93.3%), HCV-RNA were undetected but in 2 (6.7%) patients,HCV-RNA were detected again.Conclusion: Daclatasvir along with half-dose sofosbuvir are safe and effective in the treatment of CHC patients with ESRD on MHD. Half dose sofosbuvir regimen can reduce the cost of treatment of HCV in ESRD patients in developing countries like Bangladesh, where cost is a significant barrier to HCV treatment.J Bangladesh Coll Phys Surg 2023; 41: 102-107